The Type I Interferon Pathway Is Upregulated in the Cutaneous Lesions and Blood of Multibacillary Leprosy Patients With Erythema Nodosum Leprosum - Rosa, Thabatta Leal Silveira Andrezo; Mendes, Mayara Abud; Linhares, Natasha Ribeiro Cardoso; Rodrigues, Thais Fernanda; Dias, André Alves; Leal-Calvo, Thyago; Gandini, Mariana; Ferreira, Helen; Costa, Fabrício da Mota Ramalho; Sales, Anna Maria; Amadeu, Thaís Porto; Schmitz, Veronica; et al. (Frontiers in Medicine, 2022)
In leprosy patients, acute inflammatory episodes, known as erythema nodosum leprosum (ENL), complicate the course of Mycobacterium leprae infection, being responsible for high morbidity and tissue damage. In a previous study, we showed evidence implicating DNA-sensing via TLR9 as an important inflammatory pathway in ENL. A likely important consequence of TLR9 pathway activation is the production of type-I interferons (IFN-I) by plasmacytoid dendritic cells (pDCs), implicated in the pathogenesis of several chronic inflammatory diseases. In this study, we investigated whether the IFN-I pathway is activated during ENL. Blood samples and skin lesions from multibacillary patients diagnosed with ENL were collected and the expression of IFN-I and interferon stimulated genes (ISGs) were compared with samples collected from non-reactional multibacillary (NR) patients. Whole blood RNAseq analysis suggested higher activation of the IFN-I pathway in ENL patients, which was confirmed by RT-qPCR. Likewise, significantly higher mRNA levels of genes of the IFN-I pathway were detected in ENL skin biopsies when compared to lesions of NR patients. During thalidomide administration, the drug of choice for ENL treatment, a decrease in the mRNA and protein levels of some of these genes was observed, both in the skin and blood. Indeed, in vitro assays showed that thalidomide was able to block the secretion of IFN-I by peripheral blood mononuclear cells in response to M. leprae sonicate or CpG-A, a TLR9 ligand. Finally, the decreased frequencies of peripheral pDCs in ENL patients, together with the higher expression of TLR9 in ENL pDCs, and the enrichment of CD123+ cells in ENL skin lesions suggest the involvement of these cells as IFN-I producers in this type of reaction. Taken together, our data point to the involvement of the pDC/type I IFN pathway in the pathogenesis of ENL, opening new avenues for the identification of biomarkers for early diagnosis and new therapeutic targets for the better management of this type of reactional episode.